M-banking adoption from the developing countries perspective: A mediated model - Hela Ben Abdennebi (Digital Business, 2023)
This study aims to examine the factors that influence M-banking adoption from developing countries' perspective (case of Tunisia) by extending Technology Acceptance Model (TAM). To achieve this, a structural equation modelling with Partial Least Square Structural Equation Modeling (PLS-SEM) has been used to analyse the data of 202 responses. The evidence found that perceived ease of use and perceived usefulness determine the intention to adopt M-banking while perceived security, satisfaction and trust were found to be statistically insignificant in terms of their relationship with M-banking adoption intention. In this study, the empirical section examines the mediating effect of trust and satisfaction. The findings reveal that trust partially mediates the relationships between perceived security and satisfaction. Based on the research findings, managerial and theoretical implications are discussed.
Keywords: 650; M-banking; Perceived security; Satisfaction; TAM; Trust; Tunisia